Financial Performance Analysis at PT. Bata Shoes Tbk - Rizki Apriani; Amelia Fernawati; Dhea Lestari Noor Putri (Nusantara Science and Technology Proceedings, 2020)
This paper discusses the analysis of financial statements at PT Sepatu Bata, Tbk. We as authors want to analyze the ratios of financial statements and the results of analysis of financial report ratios that can measure the performance of PT Sepatu Bata, Tbk. years 2018 - 2019. From the research conducted, the analysis of financial statement ratios is to uses the ratio of liquidity and profitability. We conducted this study aimed to measure how the financial performance of PT Sepatu Bata, Tbk. By using liquidity ratios, profitability ratios. In this study, we use a quantitative descriptive approach which consists of liquidity ratios and profitability ratios as seen from the financial statements of PT Sepatu Bata, Tbk. During the 2018-2019 period. The results of this study state that liquidity from 2018 to 2019 has decreased by 38.2%. So that the company's ability to be able to pay short-term obligations has increased from 292.7% in 2018 to 330.9% in 2019. The Quick Ratio has increased the percentage from 2018 to 2019, which is 22%. So that the ratio of networking capital to current liabilities increases from 79% in 2018 to 101% in 2019. And the Cash Ratio (CR) from 2018 to 2019 has increased by 1.7%. So that the cash ratio has increased from 1.9% in 2018 to 3.6% in 2019. Profitability on the profit/loss statement of PT Sepatu Bata, Tbk. that the company can generate profits from sales (Net Profit Margin) in 2018 amounting to 6.8%, and in 2019 by 2.5%. Then the company can make a profit from every one rupiah of assets used (Return on Asset) in 2018 of 7.7%, and 2019 of 2.7%. And the company gets a return for every rupiah of owner's capital (ROE) in 2018 of 10%, and 2019 of 3.5%.